Southwest Pacific atmospheric weather regimes: linkages to ENSO and extra‐tropical teleconnections. (3rd October 2017) - Lorrey, Andrew M.; Fauchereau, Nicolas C.
ABSTRACT: We objectively identified an optimal number of atmospheric weather regimes, also called synoptic types, within the southwest (SW) Pacific tropical–subtropical domain and examined their potential drivers. Six atmospheric weather regimes in this region are characterized by spatially heterogeneous geopotential height, sea surface temperature, and regional precipitation patterns. The identified weather regimes are phase‐locked to the seasonal cycle with a moderate degree of coherency, and some are capable of persisting for weeks or more in extreme cases. Correlations between the SW Pacific weather regimes and global precipitation reanalysis fields indicate a strong connection between regional weather patterns and South Pacific convergence zone (SPCZ) mean position changes and relative intensity of convective loci within the SPCZ. Climate field correlations to SW Pacific weather regimes also show distinct geopotential height and SST signatures across Southern Hemisphere middle and high latitudes and the Indian Ocean basin. Strong statistical significance for portions of those spatial patterns lends support to the assertion of extra‐basin teleconnections for SW Pacific weather regimes. There are strong precipitation impacts from SW Pacific weather regime frequency changes and regime persistence on extreme rainfall deficits and/or surpluses for small islands during austral summer. Diagnostic analysis of the spatial correlation fields and each weather regime indicates these weather patterns are connected to eastern equatorial Pacific‐styles of El Niño and La Niña and Modoki La Niña. Another regime type appears to be connected to an enhancement of the Hadley–Ferrell circulation, while two other types are influenced by phenomena that arise outside the Pacific basin (Madden–Julian oscillation, Southern Annular Mode, and Pacific South American mode). SW Pacific weather regime investigations in the context of modern climate, palaeoclimatology, and future climate change scenarios can help to surmount spatial‐scale mismatches that exist between global models and small Pacific islands, while helping to improve general understanding of island‐scale impacts from atmospheric circulation. Abstract : Six atmospheric weather regimes have been ascribed for the southwest Pacific region. They change in frequency during different types of ENSO events and they also appear to be influenced by extra‐tropical teleconnections. There are important impacts on seasonal rainfall anomalies for several Pacific Island countries as a result of these regimes.